Towards Good Governance in Indonesia: Implementation of Good Governance at the Village Level - Fadilah, Lintang Nurul; Wijayanto, Wijayanto (Journal of Governance and Social Policy, 2025)
This study aims to determine the role of village head leadership in implementing good governance.. This study uses a descriptive qualitative research method, and data collection techniques are carried out through observation, interviews, and documentation. The theory used is the principles of good governance according to UNDP, namely accountability, transparency, and participation. The results of this study indicate that the Head of Dermaji Village has implemented the principles of good governance, namely providing transparent information about village funds and involving community elements in developing information on the village website, the village head also approaches the community directly in order to increase community participation in every policy making through hamlet deliberations or special deliberations for community groups. The obstacles faced include the village head being less firm in giving sanctions to village officials who do not comply with the timetable regulations and also being less than optimal in conducting socialization to village officials regarding the prevention of KKN practices, there is a delay in delivering information on the Dermaji village website regarding village activities because the village website account admin is only one person, then there are still some inputs from the community that have not been realized